Voltage-sensor conformation shapes the intra-membrane drug binding site that determines gambierol affinity in Kv channels. (August 2016) - Kopljar, Ivan; Grottesi, Alessandro; de Block, Tessa; Rainier, Jon D.; Tytgat, Jan; Labro, Alain J.; Snyders, Dirk J.
Abstract: Marine ladder-shaped polyether toxins are implicated in neurological symptoms of fish-borne food poisonings. The toxin gambierol, produced by the marine dinoflagellate Gambierdiscus toxicus, belongs to the group of ladder-shaped polyether toxins and inhibits Kv3.1 channels with nanomolar affinity through a mechanism of gating modification. Binding determinants for gambierol localize at the lipid-exposed interface of the pore forming S5 and S6 segments, suggesting that gambierol binds outside of the permeation pathway. To explore a possible involvement of the voltage-sensing domain (VSD), we made different chimeric channels between Kv3.1 and Kv2.1, exchanging distinct parts of the gating machinery. Our results showed that neither the electro-mechanical coupling nor the S1-S3a region of the VSD affect gambierol sensitivity. In contrast, the S3b-S4 part of the VSD (paddle motif) decreased gambierol sensitivity in Kv3.1 more than 100-fold. Structure determination by homology modeling indicated that the position of the S3b-S4 paddle and its primary structure defines the shape and∖or the accessibility of the binding site for gambierol, explaining the observed differences in gambierol affinity between the channel chimeras. Furthermore, these findings explain the observed difference in gambierol affinity for the closed and open channel configurations of Kv3.1, opening new possibilities for exploring the VSDs as selectivity determinants in drug design. Graphical abstract: Highlights: The S3b-S4 part of the voltage sensor domain affects gambierol affinity in Kv3.1. The conformation and primary structure of S3b-S4 shapes the size of the binding site. VSDs can determine drug selectivity to develop novel Kv channel modulators.